Design and implementation of a low power spike detection processor for 128-channel spike sorting microsystem - Tsung-Chuan Ma; Tung-Chien Chen; Liang-Gee Chen (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2014)
It is impractical to apply a general spike sorting algorithm for every subject because of the individual characteristics of brain signal. Furthermore, extracting more neural activities for higher accuracy of spike sorting requires more input electrodes as well as large power consumption and chip area. Therefore, several practical constraints are considered in this work when implementing a programmable spike sorting hardware with large number of input channels. In this paper, we provide a 128-channel spike detection processor for spike sorting microsystem without compromise of the power efficiency. This chip consumes only 87.02uW and 9.7uW/mm 2 of power density, fabricated with 90nm low-leakage CMOS process.